Patient survival after acute myocardial infarction treated with primary percutaneous coronary intervention within the left main coronary artery according to time of admission. (25th November 2020) - Januszek, R; Bujak, K; Gasior, M; Dudek, D; Bartus, S
Abstract: Background: Previously published studies assessing the time effect of primary percutaneous intervention (PCI) on long-term clinical outcomes in an overall group of patients with acute coronary syndromes has been widely investigated. It has been suggested that night-time admission may negatively influence long-term overall mortality. Patients treated within the left main coronary artery (LMCA) belong a narrow group of high-risk procedures that require an operator and a team with high skills. Purpose: The aim of the presented study was to assess the relationship between the time of pPCI (day- vs. night-time) and overall mortality among patients treated due to AMI within the LMCA. Methods: This observational study was performed on 443, 805 patients hospitalised due to non-ST segment elevation myocardial infarction (NSTEMI) or ST-segment elevation myocardial infarction (STEMI). Patients were prospectively enrolled between January 2006 and December 2018 in the ongoing Polish Registry of Acute Coronary Syndromes (PL-ACS). From the overall group of patients, the authors selected 5, 404 patients treated within the LMCA. After taking exclusion criteria into consideration, the patients were divided according to time of PCI treatment: daytime hours (7:00 a.m.-10:59 p.m.) – 2, 809 patients and night-time hours (11:00 p.m. - 6.59 a.m.) – 473 patients. Results: Patients treated during night-time and daytime did not differ significantly in age (70.79 [61.52–79.73] vs. 69.73 [60.8–78.82] years, p=0.13) or gender – males (67.6% vs. 67.0%, p=0.79). Patients treated during daytime presented with significantly higher rate of STEMIs (67.2% vs. 49.9%) and lower rate of NSTEMIs (32.8% vs. 50.1%) in comparison to those treated during night-time (p<0.001). The 30-day and 12-month overall mortality rates were significantly greater among patients treated during night-time hours (20.3% vs. 14.9%, p=0.003) and (31.7% vs. 26.2%, p=0.001). Kaplan-Maier survival curves confirmed this relationship (p=0.001). Multiple regression analysis did not confirm that the time of pPCI (day- vs. night-time) is significantly related to survival (hazard ratio [HR]: 1.22; 95% confidence interval [CI]: 0.96–1.55, p=0.099). However, significance was achieved for the left ventricle ejection fraction (HR: 0.95; 95% CI: 0.94–0.95, p<0.001), systolic blood pressure on admission (HR: 0.995; 95% CI: 0.991–0.998, p=0.005), age (HR: 1.04; 95% CI: 1.03–1.05, p<0.001), the use of intra-aortic balloon counterpulsation (HR: 1.04; 95% CI: 1.03–1.05, p<0.001) and diagnosed peripheral artery disease (HR: 1.55; 95% CI: 1.2–2.01, p<0.001). Conclusions: The time of pPCI (day- vs. night-time) in patients with AMI and treated within the LMCA is related to the overall 30-day and 12-month survival which is poorer in those treated during the night-time. However, this relationship was not confirmed by multiple regression analysis and was not found to be significant among other stronger predictors. Funding Acknowledgement: Type of funding source: None